"Empirical corporate finance: Opportunities and challenges" : editorial synthesis of the special issue - Philip Sinnadurai (Journal of Risk and Financial Management, 2022)
This concept paper synthesises the special issue with an integrated discussion of all four papers published therein, from the viewpoint of the theme of this special issue: opportunities and challenges for future empirical research in corporate finance. The four papers highlight that future empirical research faces the challenge of acknowledging fundamental paradigms in the literature. These include analytical models of capital structure, agency theory, the literature on Initial Public Offering anomalies and earnings valuation. An opportunity for future empirical research is to use these foundations to contribute to emerging paradigms. The latter include the empirical evidence of the shareholder wealth effects of government investment, managerial overinvestment and the acknowledgement of unlisted entities within capital markets research.
Keywords: 650; valuation; corporate finance; capital structure; agency theory; government shareholding; Initial Public Offerings; overinvestment; private companies